Revealing Power in Truth; Comment on "Knowledge, Moral Claims and the Exercise of Power in Global Health" - Kelley Lee (Kerman University of Medical Sciences, 2015)
Jeremy Shiffman's editorial appropriately calls on making all forms of power more apparent and accountable, notably productive power derived from expertise and claims to moral authority. This commentary argues that relationships based on productive power can be especially difficult to reveal in global health policy because of embedded notions about the nature of power and politics. Yet, it is essential to recognize that global health is shot through with power relationships, that they can take many forms, and that their explicit acknowledgement should be part of, rather than factored out of, any reform of global health governance.